2015
DOI: 10.1093/pm/pnv056
|View full text |Cite
|
Sign up to set email alerts
|

Improving Trainee Competency and Comfort Level with Needle Driving Using Simulation Training

Abstract: Our study demonstrates that simulation training may improve both trainee comfort level and competency with needle driving. After a brief lecture and a 30-minute training session with the simulator, subjective comfort measures and competency measures (more subjects were able to reach the target, vertical and horizontal deviations from the target decreased) were significantly improved. This suggests that simulation may be a helpful tool in teaching needle driving skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The authors thus concluded that a joint injection simulator appears to be an appropriate teaching aid to allow repeated training with the aim of acquiring the technical skills and con dence in the abilities in performing such procedures. This assertion substantiates the ndings of Chen et al [38] that have demonstrated the e ciency of simulation training in improving both the subjective comfort level and objective measurements of the skills required in performing injections among anaesthetic procedures. Meanwhile, the results from the studies carried out by Berman et al [32] and Gormley et al [22] suggest than practicing on a real body or human corpse provide slightly better learning curves than other designs of training courses, while the differences have not been found as statistically signi cant in the article by Fox et al [34] when comparing the cadaver group to the synthetic model one.…”
Section: Discussionsupporting
confidence: 89%
“…The authors thus concluded that a joint injection simulator appears to be an appropriate teaching aid to allow repeated training with the aim of acquiring the technical skills and con dence in the abilities in performing such procedures. This assertion substantiates the ndings of Chen et al [38] that have demonstrated the e ciency of simulation training in improving both the subjective comfort level and objective measurements of the skills required in performing injections among anaesthetic procedures. Meanwhile, the results from the studies carried out by Berman et al [32] and Gormley et al [22] suggest than practicing on a real body or human corpse provide slightly better learning curves than other designs of training courses, while the differences have not been found as statistically signi cant in the article by Fox et al [34] when comparing the cadaver group to the synthetic model one.…”
Section: Discussionsupporting
confidence: 89%
“…This study is consistent with prior research that demonstrates utility of simulation training in PM&R education. Simulation techniques have been applied broadly within PM&R education, with studies showing successful use in the instruction of musculoskeletal ultrasound, needle driving for interventional procedures, pressure ulcer and patient safety education, botulinum toxin injections and peripheral motor blocks, among others . Pilot studies have reported the feasibility of using simulation‐based education for teaching autonomic dysreflexia, a common urgent medical complication that occurs in patients with complete spinal cord injuries at T6 or above, to PGY‐2 PM&R residents .…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training aims to mimic real‐life experience and is consistently associated with positive effects on knowledge, skills, and patient‐related outcomes . There is good evidence to support the use of simulation‐based methods in PM&R education . However, little evidence exists on the use of simulation technology for the instruction of urgent medical complications to PM&R residents .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis was generally appropriate for study design, except one study which gave no quantitative analysis of the data obtained [34]. From a complexity viewpoint, 7 studies gave only descriptive analysis [23,27,30,[33][34][35][36], whereas the other 7 studies gave a more complex and in-depth analysis of their data [24][25][26]28,29,31,32]. MERSQI scores were generally closely matched to the outcomes which had been drawn out of the studies as a separate data-point during data collection.…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…Simulation, a simulator device, or a phantom anatomy (e.g. spinal-epidural manikin [37]) was the main educational intervention for 8 of the 14 studies [24,26,28,30,[33][34][35]. 226 trainees were included in the studies examining simulation.…”
Section: Simulationmentioning
confidence: 99%